Green Innovation and CSR Index analysis on Firm Value with Financial Performance Variable as Mediating Variable in Manufacturing Companies - Puji Estuti, Eni; Nafiar, Zumrotun; Sundari, Pipit (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Firm value is a primary determinant for potential investors as it reflects the company's condition. It is crucial for investors to focus on firm value because it is their main objective to invest in profitable companies. This study uses a quantitative method with Partial Least Squares (PLS) analysis. The results show that the CSR Index has a positive and significant influence on firm value, while green innovation does not affect firm value. Return on Asset (ROA) is able to mediate the influence of the CSR Index on firm value. However, ROA is unable to mediate the influence of green innovation on firm value in manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2022 period.